A Review on Dry-powder Inhaler: A Review on Dry-powder Inhaler - Jadhav, S. Y. (International Journal of Pharmaceutical & Biological Archive, 2020)
In recent years, the pulmonary drug delivery system is found to be preferred route of administration for various drugs. It has been divided into three classes: Nebulizers, pressurized metered-dose inhalers, and dry-powder inhaler (DPI). This article focuses on the DPI formulation, principle of working, DPI devices, and evaluation parameters. DPI formulations consist of micronized drug blended with larger carrier particles, which enhance flow, reduce aggregation, and aid in dispersion. DPIs are commonly used to treat respiratory diseases such as asthma, bronchitis, and chronic obstructive pulmonary disease. DPI is formulated using four types of formulation strategies such as carrier-free, drug carrier, drug additive, and drug-carrier additive. The particle size of active pharmaceutical ingredients must be present in size range about 1–5 μm which also guarantee that the patient gets the same dose every time at different airflow rate. A DPI is a device that delivers medication to the lungs in the form of a dry powder. DPI devices can be categorized as capsule-based, blister based, canister/cartridge-based, and other types.